Application of modified wavelet and homotopy perturbation methods to nonlinear oscillation problems - Selvi, M. Salai Mathi; Rajendran, L. (Applied mathematics and nonlinear sciences, 2019)
In this paper, an accurate and efficient Chebyshev wavelet-based technique is successfully employed to solve the nonlinear oscillation problems. Numerical examples are also provided to illustrate the efficiency and performance of these methods. Homotopy perturbation methods may be viewed as an extension and generalization of the existing methods for solving nonlinear equations. In addition, the use of Chebyshev wavelet is found to be simple, flexible, accurate, efficient and less computational cost. Our analytical results are compared with simulation results and found to be satisfactory.